Evaluating Differentiated Chemistry Instruction in Senior High Schools Using Stake’s Countenance Model: A Study in Gorontalo City - Suryanto, Suryanto; Lukum, Astin; La Kilo, Akram; Laliyo, Lukman A.R.; Pikoli, Masrid; Salimi, Yuszda K. (Jambura Journal of Educational Chemistry, 2025)
This study aims to evaluate the implementation of differentiated instruction in Chemistry subject for Grade 10 students across senior high schools in Gorontalo City using Stake’s Countenance Model. The evaluation focused on three key components: antecedent (lesson planning), transaction (instructional implementation), and outcome (student learning results). Data were collected through the analysis of lesson plans and teaching modules, classroom observations, teacher interviews, and assessments of student learning outcomes. The analysis employed both congruence and contingency approaches. The findings indicate that both lesson planning and instructional implementation fall into the "moderate" category, with average scores of 69.82% and 67.52%, respectively, while student learning outcomes were categorized as "good" with an average score of 68.89%. The contingency analysis revealed a misalignment between antecedent and transaction with the outcome, suggesting that student achievement was more strongly influenced by administrative targets (KKTP) rather than the effectiveness of differentiated instruction strategies. This study recommends the need for pedagogical training focused on strengthening conceptual understanding of differentiation, designing adaptive instructional materials, and applying authentic assessment practices to promote inclusive and responsive learning tailored to diverse student needs.